Examining influencer marketing: the roles of para-social relationships, unpaid collaborations, and trustworthiness in shaping consumer buying behavior - Nada Sarkis; Nada Jabbour Al Maalouf; Ramy El Lakiss (Cogent Business & Management, 2024)
The marketing landscape has intensely changed with the rise of digital platforms and social media. Social media influencer marketing was found by many previous studies to be a significant factor in shaping consumer buying behavior. This explanatory study investigates the impact of influencer marketing including para-social relationships, unpaid collaborations, and influencer trustworthiness on Lebanese consumers buying behavior. A quantitative analysis was employed using data collected through a questionnaire from a sample of 250 respondents. The findings revealed that para-social relationships and unpaid collaborations have a positive impact on Lebanese consumer buying behavior. The study contributes significantly by providing insights into the Lebanese market. By applying the Stimulus-Organism-Response Theory and Social Learning Theory, the study enriches the theoretical understanding of influencer marketing. Practically, it offers actionable strategies for marketers, emphasizing the importance of influencer marketing in driving consumer buying behavior in Lebanon.
Keywords: 650; Influencer marketing; buying behavior; trustworthiness; para-social relationships; unpaid collaboration